THE USE OF U-DICTIONARY APPLICATION TO IMPROVE VOCABULARY MASTERY OF THE EIGHTH GRADE STUDENTS OF SMP NEGERI 17 PALU - Nurul Adha, Gita; Rita, Ferry; Mashuri, Mashuri (Tadulako University, 2024)
The objective of this research is to improve if using the U-Dictionary Application can improve the vocabulary of eighth-grade students. The researchers applied quasi experimental research design. The experimental group consisted of 25 students, while the control group also consisted of 25 students. The data were collected using a test administered twice; it was in the form of a pre-test and a post-test. The data were analyzed statistically. The results of the data analysis showed that the t-counted value (2.14) was higher than the t-table (1.677). It means that the hypothesis is accepted. In other words, using U-Dictionary Application can improve the vocabulary of eighth-grade students of SMP Negeri 17 Palu.